OPIOIDERGIC AND CHOLINERGIC BUT NOT NITRIC OXIDE PATHWAYS ARE INVOLVED IN ANTINOCICEPTIVE ACTIVITY OF VITEX AGNUS-CASTUS ESSENTIAL OIL IN THE ACUTE TRIGEMINAL MODEL OF PAIN IN RAT - Khalilzadeh, Emad; Hazrati, Reza; Vafaie Sayah, Gholamreza; Hasannejad, Hamideh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Vitex agnus-castus (VAC) and its essential oil traditionally used to treat many conditions and symptoms such as premenstrual problems, mastalgia, inflammation, sexual dysfunction and pain. This study was conducted to investigate the analgesic effect of essential oil extracted from VAC (EOVAC) leaves in acute trigeminal model of nociception in adult male Wistar rats. Furthermore, possible involvements of opioidergic, cholinergic and L-arginine/NO/cyclic GMP pathway in analgesic activity of EOVAC were investigated. Methods: The EOVAC was extracted from powdered plant material by hydro-distillation in a Clevenger type apparatus. Acute trigeminal pain was induced by putting a drop of NaCl 5 M solution (40 Î¼l) on the corneal surface of the eye and the numbers of eye wipes counted during the first 30 seconds. Results: EOVAC at doses of 100 and 200 mg/kg subcutaneous and morphine 2.5 and 5 mg/kg i.p. produced a significant anti-nociceptive effect in this model of corneal pain. Naloxone (1 mg/kg i.p.) and atropine (1 mg/kg i.p.), L-arginine (100 and 200 mg/kg i.p.) and methylene blue (5 and 10 mg/kg i.p.) alone had no any effect in the acute corneal pain. Pretreatment with naloxone or atropine significantly reversed the EOVACâ€‘induced analgesia, but L-arginine (300 mg/kg) and methylene blue (5 mg/kg) did not change the suppressive effect of EOVAC on pain response. Conclusion: The present results suggest that the EOVAC produced anti-nociception in the acute corneal pain through mechanisms that involved both opioidergic system and/or the cholinergic system, but not via L-arginine/NO/cyclic GMP pathway, supporting the folkloric usage of the plant to treat various painful processes. Keywords: Acute trigeminal pain, Vitex agnus-castus essential oil, Opioidergic system, Cholinergic system, Rat.